CHARACTERISTIC DIFFERENCES OF ARABICA GREEN BEANS OBTAINED FROM DIFFERENT ALTITUDE AND PRODUCTION OF FERMENTED ARABICA GREEN BEAN USING GREEN BEAN FROM HIGH ALTITUDE - Amalia, Fitri
Arabica is one of coffee species that popular based on its taste. Arabica coffee is grown high altitude at 1000-2100 m above sea level. The Arabica coffee that planted at higher altitude, the better the quality of Arabica coffee. Due to low temperature, its slow coffee fruit maturation and promote accumulation of compounds that related to taste in coffee beans. The fermentation process also affects the Arabica coffee quality to become more acidic with fruity notes and less bitter. The standardized fermentation process in coffee processing is applied to prevent over-fermentation that caused coffee off-flavor. Standardized fermentation process also applied to produces coffee beans with unique taste by using starter culture containing bacteria with particular abilities such as lactic acid bacteria, cellulolytic bacteria, and amylolytic bacteria. Those bacteria with those abilities were used to breakdown the polysaccharides, the largest constituent in green coffee beans that make up 48-60% of green coffee beans dry weight. Various chemical compounds are used to study the effect of altitude and the fermentation process on coffee flavor. However, the chemical compound used, such as caffeine, chlorogenic acids, fatty acids, and sugar content, showed various result and lead to difficulties to conclude the effect of altitude and fermentation on coffee flavor. Metabolomics is a study that perform global analysis of metabolite on a target organism and various of metabolite could be detected at one time. In this study, metabolomic analysis using gas chromatography/mass spectrometry (GC/MS) was used to observe the differences of metabolome profile in green coffee beans obtain from different altitude. Metabolomic analysis also used to observe the differences of metabolome profile of green coffee beans between fermented beans and non-fermented ones with green coffee beans from high altitude as raw materials. The result of metabolomic analysis were visualized using principal component analysis (PCA). The PCA results shows the largest variation in principal component 1 is 54.4%. In the PCA score plot, the green coffee beans were clustered based on altitude, green coffee beans obtained from low altitude (400 and 800 m above sea level (masl)) and from high altitude (1200-1500 masl). Based on variable loading value in PCA loading plots, glucarate, melezitose, and serotonin are thought to be correlated with green coffee beans from low altitude. Galactose, mannose and glucose have the highest positive loading value and are thought to be correlated with green coffee beans from high altitude. The differences in relative intensity of those metabolites between low altitude and high altitude green coffee beans showed to be significant with p-value <0.001 and <0.01. Green coffee beans from high altitude (1000, 1200, 1400, and 1600 masl) were analyzed using metabolomic approach and visualized by PCA. The PCA results showed the largest variation in principal component 1 by 30.9%. The PCA score plot showed samples clustering of green coffee beans obtained from 1000 masl and more than 1000 masl. In the PCA loading plots, glycine and several saccharides such as fructose, glucose, galactose and glucose, psicose and tagatose, have negative loading value and thought to be correlated with green coffee beans obtained from 1000 masl. Phenylalanine, inositol, and tyrosine have positive loading values and are thought to be correlated with green coffee beans obtained from more than 1000 masl in altitude. The differences in the relative intensity of metabolites that are thought to correlated with sample clustering showed significant differences with p-value <0.01 and <0.05. The difference in the relative intensity of galactose and mannose, the metabolites thought to correlate with green coffee beans from the high altitude, was also observed and found a significant difference with the p-value <0.05 between coffee beans obtained from an altitude of 1600 masl with coffee beans obtained from a height of 1000, 1200, and 1400 masl. Greenn coffee beans from 1000, 1200, 1400 and 1600 masl were used as raw materials for standardized fermentation using starter cultures containing bacteria with amylolytic, pectinolytic and proteolytic abilities by bacteria BF5C (2) and AF7E as well as bacteria with cellulolytic ability by UciSp14. Starter cultures were prepared with more cellulolytic bacteria with a ratio of BF5C (2): AF7E: UciSp14 (1: 1: 3). This is based on the consideration that 48-60% of the dry weight of green coffee beans are polysaccharides with 23% and 12.7% in the form of hemicellulose and cellulose. Green coffee beans with standardized fermentation and non-fermented coffee beans are analyzed using metabolomics to see differences in metabolite profiles of both types of coffee beans. Green coffee beans, fermentation and non-fermentation, then roasted to be sensory analyzed by cupping test. Roasted coffee beans used for cupping tests were analyzed by metabolomics to observe the profile of their metabolites. The results of metabolomic analysis are visualized by PCA. PCA results in fermented and non-fermented coffee beans indicate the greatest variation in principal component 1, which is 24.1%. In the PCA score plot, green coffee beans are clustered by type of coffee beans, fermented coffee beans and non-fermented coffee beans. In PCA loading plots, metabolites that have a negative loading value and are thought to correlate with non-fermented coffee beans are galactinol. Saccharide compounds along with 2-aminoethanol, adenine and lysine have positive loading values and are thought to correlate with fermented green coffee beans. Saccharide compounds annotated as galactose, galactose and glucose and galactinol had significant differences in relative intensity between fermented and non-fermented coffee beans with p-value <0.01. The results of sensory analysis of roasted coffee beans indicate that both fermented and non-fermented coffee beans have more than 80 cupping scores and are included in the specialty coffee classification. Fermented coffee beans with raw materials of green coffee beans from 1000 and 1600 masl in altitude have decreased cupping scores to 84.25 and 83.56 when compared to non-fermented coffee beans, 84.92 and 83.58 respectively. Fermented coffee beans with raw materials of green coffee beans from 1200 and 1400 masl have increased cupping scores to 84.94 and 84.72 compared to non-fermented coffee beans, 83.42 and 84.08 respectively. The fermentation process causes the appearance and / or loss of flavor description. This is in accordance with the results of previous studies. Description of the taste of lemony, bright acid, and brown sugar are commonly found in coffee beans with standardized fermentation. This is because the degradation of polysaccharides into saccharide compounds which are further degraded in the roasting process become acidic compounds that play a role in the acid taste in coffee. The results of metabolomic analysis of roasted coffee beans are visualized by PCA. The PCA results show the two biggest variations in principal component 1 is 44.8% and 13.1% in principal component 2. In the PCA score plot, the samples are clustered into two groups. the first group consisted of non-fermented coffee from 1600 masl and fermented coffee with coffee beans from 1200, 1400 and 1600 masl. This group has similarities in taste, namely caramelly, nutty, spicy, bright acidity, and brown sugar. The metabolites which are thought to correlate in the first group consist of unknown compounds and saccharide compounds and chlorogenic acid is detected in PCA loading plots. The second group consisted of non-fermented coffee from 1000, 1200, and 1400 masl and fermented coffee with coffee beans from 1000 masl. This group has similarities that are astringent and spicy. The metabolite that correlates in the second group consists of unknown compounds, organic acids and sugar alcohol. Based on metabolomic results, altitude factors and standardized fermentation processes caused different profiles of metabolites in Arabica coffee beans. This difference in the profile of metabolites is thought to correlate with the final flavor of Arabica coffee. With the metabolomic approach, this study can provide a picture of the differences in the profile of metabolites that occur because altitude and fermentation process correlate with changes in the taste of Arabica coffee.